Social and Economic Development of Koya Village: A Historical Study (2015-2023) - Yolanda, Yolanda; Nuraedah, Nuraedah; Nadjamuddin, Lukman; Nongtji, Minarni (Universitas Pahlawan Tuanku Tambusai, 2025)
This article examines the social and economic development of Koya Village, Petasia District, North Morowali Regency, Central Sulawesi, during the period 2015–2023. The study employs a qualitative approach with historical methods, including field observations, in-depth interviews, and document analysis. Findings indicate that social development in Koya Village is characterized by adjustments to norms, morals, and traditions, the emergence of new communication patterns, and changes in intergenerational relationships. Economic transformation is marked by a shift from traditional agriculture and fisheries to industrial and service sectors, particularly after the establishment of the Gunbuster Nickel Industry (GNI) mining company. Furthermore, the development of mangrove ecotourism in Tomori Bay has provided new opportunities for local community empowerment. While these transformations have brought positive impacts such as improved welfare, they also created challenges including dependency on mining, social inequality, and the weakening of communal values such as mutual cooperation. Overall, the people of Koya demonstrate adaptive capacity by combining traditional values with modernity, although sustainable development strategies are still needed to balance social, cultural, economic, and environmental aspects.